2001
DOI: 10.1023/a:1026654317094
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cultural beliefs have been hypothesized to be powerful barriers to breast cancer screening in minority women and physician recommendation is consistently reported to be the strongest incentive. This study investigated (1) beliefs regarding breast cancer and (2) the perception of barriers to mammography and clinical breast examination in a sample of immigrant Tamil women, as well as in a sample of primary care physicians. Three focus groups, each consisting of 10 immigrant Tamil women from Sri Lanka aged 50 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Neither cancer nor intimate body parts are commonly discussed in some South Asian cultures. 42 46 All studies showed that women lacked basic understandings of cancer, cancer prevention or early detection. Breast cancer was viewed by some women as a ‘ white woman’s disease’ 41 that did not occur in their community.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neither cancer nor intimate body parts are commonly discussed in some South Asian cultures. 42 46 All studies showed that women lacked basic understandings of cancer, cancer prevention or early detection. Breast cancer was viewed by some women as a ‘ white woman’s disease’ 41 that did not occur in their community.…”
Section: Resultsmentioning
confidence: 99%
“…First, religious fatalism meant that cancer was seen as predestined, as divine retribution for sins or as a dearth of moral character. 42 Second, all studies pointed to the curative focus of healthcare in countries of origin as a reason for some women’s failure to understand the concept of prevention 42 48 and consequent belief that healthcare seeking is unnecessary in the absence of symptoms. 41 44 46 49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness and health seeking practices have been shown to be poor in many developing countries, necessitating the need for proper awareness programs [8,9]. The only published study from Sri Lanka, conducted in a population of Tamil immigrants, identified poor knowledge and cultural conservatism as barriers in implementing breast cancer screening programmes [10]. …”
Section: Introductionmentioning
confidence: 99%
“…The differences in levels of cancer fear and fatalism across ethnic groups suggest that other cultural factors, such as language spoken and migration status, may have a role in explaining variations in these variables. For some ethnic groups, language barriers may impede understanding of the preventive purpose of cancer screening tests, which may increase levels of cancer fear when offered one ( Meana et al , 2001 ; Austin, 2009 ). Language barriers may also have a role in perpetuating fatalistic beliefs: 62% of Spanish-speaking Latinos believed that cancer was not preventable, vs 40% of English-speaking Latinos ( Ramírez et al , 2013 ).…”
mentioning
confidence: 99%